コクリツ キョクチ ケンキュウジョ ノ デンシ ケイサンキ システム - 神沼, 克伊; カミヌマ, カツタダ; 内海, 達郎; ウツミ, タツロウ; Kaminuma, Katsutada; Utsumi, Tatsuro (国立極地研究所, 1977)
P(論文) 国立極地研究所に新しい設備として中型電子計算機が導入された.この電子計算機の導入にあたっては,一般科学技術計算が容易にできる十分なアプリケーションプログラムが用意されていることに加え,次の諸点が考慮された.1)極地研究のデータセンターとしての役割がはたせるデータバンクの建設が可能なこと.2)多目的に使える画像処理システムがあること,3)遡及検索の可能な文献検索システムがあることなどである.すなわち,極地研究の共同利用研究所である以上,極地研究所の所員はもとより,外部の研究者にも十分利用できるような豊富なシソーラスと,使い易さを兼ね備えるよう配慮した.導入した電子計算機はHITAC M-160 II(主記憶容量512 Kバイト)であり,画像処理システムとしては,日立電子からプログラマブルユニット,イメージプロセッサーなどを導入した. A new computer system was installed at the National Institute of Polar Research (NIPR) in December 1976. The fundamental criterion to construct the machine system is that useful application programs for scientific researches are available. The following criteria are also important because NIPR is the only one institute of cooperation for researching the polar sciences in Japan: 1) The possibility to establish a data bank system as a data center of polar researches in Japan. 2) The possibility to install an image processor system for using many purposes. 3) The possibility to install a document retrieval system. The computer system of HITAC M-160 II is chosen as the new system. The image processor unit was also installed. The data bank has the information of gravity, meteorology, geology, meteorites, biology and so on. The digital data of maps are also installed, and those are the maps of world, Japanese Islands, Antarctica, Ongul Islands, etc. The document tapes of Antarctic Bibliography are supplied by the Library of Congress, U.S.A. departmental bulletin paper